E-Report Revolution: Web Prototyping for Vocational High Schools in Bandung - Fauka, Ahfi; Yuliana, Mila; Syukri, Muhammad; Risanti, Rini (LPPM STMIK Mardira Indonesia, 2024)
The report is a crucial document that thoroughly documents pupils' learning outcomes in both academic and extracurricular domains. Inputting many student grades into reports by hand takes a long time, and parents cannot constantly check their children's report cards. The author hopes to make data entry easier and allow parents to monitor their children's academic progress with the web-based e-report information system that uses the prototyping technique. The author used JavaScript, PHP, and a MySQL database to create an online e-report information system. This approach is intended to help homeroom instructors and teachers at one of Bandung's vocational high schools manage grades and determine their pupils' average scores. This study emphasizes the potential for increasing grade management effectiveness, fostering better parent-school communication, and offering a clearer picture of student performance. It might also inspire other academic institutions to implement comparable technology to expedite their reporting procedures.